Free convection in a porous medium with newtonian heating on a vertical surface - Bocharova, Anna Albertovna; Plaksina, Irina Vladimirovna (Computational Continuum Mechanics, 2008)
The free convection flow along a vertical surface in a porous medium with Newtonian heating is studied under boundary conditions of the third kind. The order-of-magnitude analysis is worked out to determine the range of applicability of the boundary layer approximation for the system of governing equations. The temperature and stream function fields are described by applying asymptotic expansions valid near the leading edge and valid far downstream.